PENANGGULANGAN PRAKTIK CYBER PROSTITUTION PADA APLIKASI MICHAT BERDASARKAN KEBIJAKAN KRIMINAL DI INDONESIA - Sindi Fitria; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2022)
Prostitution is a despicable act because it violates the norms that live and develop in society,especially moral norms. One of the crimes that is a concern in today's society is prostitution in thecyber world (cyber prostitution). Along with the increasingly widespread use of the internet inIndonesia, cyber prostitution activities are also developing. The perpetrators and pimps began touse social networking sites such as MiChat to carry out their actions. MiChat which wasoriginally used for friendship, is now used to market sex transactions. Cyber prostitution cases inIndonesia currently require a criminal law policy in an ef ort to overcome this. The regulationsgoverning this problem are the Law on Information and Electronic Transactions, the Law onPornography and the Criminal Code. This research is a descriptive normative legal research witha statutory approach, namely examining the laws and regulations related to the legal issues raisedand with an analytical approach. The results of this study indicate non-penal countermeasures,government institutions have carried out supervision or monitoring of applications that are oftenused as media for cyber prostitution. Meanwhile, legally, the Criminal Code and the ITE Law donot clearly regulate the definition of online prostitution.